Improved small signal model for voltage‐boosting converter with hybrid energy pumping. Issue 4 (1st April 2015) - Faqiang, Wang; Shan, Miao; Xikui, Ma
Abstract : Voltage‐boosting converter with hybrid energy pumping, which possesses high voltage conversion, small voltage stress on the low‐side switch and diode and easy to drive, is a good topology of DC–DC converters for obtaining high output voltage to satisfy the requirements in practical applications. In this study, after indicating the drawbacks of the existing small signal model of the voltage‐boosting converter with hybrid energy pumping from the comparisons between the theoretical calculations and the power electronics simulator (PSIM) simulations, an improved small signal model and corresponding transfer functions of this new converter in continuous conduction mode and discontinuous conduction mode operations are derived and analysed. The results from the theoretical analysis, PSIM simulations and circuit experiments show that the improved small signal model of the voltage‐boosting converter with hybrid energy pumping here is more effective, accurate and general than the existing model.